Bolokuncoro: Photographic Story Media in Interactive Learning Introduction to Local Culture Literacy for Early Childhood Students - Fajrie, Nur; Nofeca, Ysta; Utaminingsih, Sri; Aliriad, Hilmy (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
The books used by teachers in the learning process regarding the introduction of cities are less attractive to students. When using books at school, teachers experience problems because books are still conventional so they are easily damaged when used frequently. The purpose of this study was to develop a media for learning the picture story 'Bolokuncoro' in an interactive learning introduction to local cultural literacy for early childhood students. This research uses the Research and Development (R&D) method adopted from the Borg and Gall model with a small scale, namely 7 stages of research. The results of this study are the percentage validation test. The final validation results of the material obtain an average percentage of 88%. The percentage is included in the very feasible and usable category. While the average percentage of media validation is 86%. The percentage is included in the very feasible and usable category. However, there are some suggestions that can be applied by researchers and if they are not implemented too. During the field test using the teacher's response questionnaire. The final score based on the total score divided by the maximum score obtained an average of 96% with a very decent category. So that the media can be used in learning.